Trade barriers and export growth: Analyzing the US-China trade relationship with the LSDV model - Yang, Ting; Lau, Wee-Yeap; Bahri, Elya Nabila Abdul (Asian Development Policy Review, 2025)
This study employs a gravity model of trade to assess the repercussions of US-China trade frictions on China's export dynamics. Our findings unravel some noteworthy results: First, we find a significant and negative correlation between the variables linked to trade frictions, namely Technical Barriers to Trade (TBT) and Average Tariff (AT), and the volume of China's exports. Secondly, the regression results do not indicate that the SPS has a dampening effect on China's exports. Thirdly, China's exports are more affected by the Average Tariff (AT) than by Technical Barriers to Trade (TBT). Finally, the exports from the previous period positively influenced China's exports to the US. In other words, the US-China trade friction has significantly reduced China's exports to the US. As a policy implication, China should reduce its dependence on the US market, diversify its markets, uphold the principles of free trade and multilateralism, and promote openness in response to the challenges of the trade war.